Evidence‐based treatments for rosacea based on phenotype approach. (1st July 2019) - van Zuuren, E.J.; Fedorowicz, Z.; Tan, J.; van der Linden, M.M.D.; Arents, B.W.M.; Carter, B.; Charland, L.
Summary: Rosacea is a common, chronic skin condition causing flushing, redness, red pimples and pus‐filled spots (pustules) on the face. It affects about 1‐20% of people worldwide. Rosacea can also cause inflammation of the eyes/eyelids (ocular rosacea) and thickening of the skin, especially the nose (rhinophyma). Although the cause of rosacea is unclear, treatments are available for this distressing disease. This review from the Netherlands, U.K. and Canada aimed to find out which treatments are effective for rosacea. The authors included data from 152 studies. For reducing redness, brimonidine and oxymetazoline worked from three up to 12 hours after being applied. For reducing pimples and pustules with topical (applied to the skin) treatments, azelaic acid, ivermectin and metronidazole were effective and safe. Ivermectin was slightly more effective than metronidazole. Minocycline foam also showed a large reduction in pimples and pustules. With oral (taken by mouth) antibiotics, tetracycline, doxycycline 40 mg or minocycline 45 mg reduced the number of pimples and pustules. Doxycycline 40 mg was likely as effective as 100 mg, with fewer side effects like diarrhoea and nausea. Oral minocycline 100 mg was as effective as doxycycline 40 mg. Azithromycin may be as effective as 100 mg doxycycline. Isotretinoin 0.25 mg/kg decreased pimples and pustules by 90%, and increased quality of life and patients' satisfaction. Isotretinoin 0.3 mg/kg appeared to be slightly more effective than 50‐100 mg doxycycline. However, isotretinoin is known to cause serious birth defects, so pregnancy must be avoided when using it. For treating dilated blood vessels, laser therapy and intense pulsed light therapy were both effective, but these studies had limited data. In ocular rosacea, ciclosporin 0.05% ophthalmic emulsion increased quality of life and improved the amount/quality of tears, and was slightly more effective than oral doxycycline. Omega‐3 fatty acids likely improve dry eyes and tear gland function. Abstract : Linked Article: van Zuuren et al. Br J Dermatol 2019; 181 :65–79